CSPINE (Correlating Soft tissue Projections in Injured NEcks) A descriptive study on measuring prevertebral soft tissue thickness as a ratio of vertebral body width in paediatric cervical spine trauma - McCaul, Jeannie Katharine (Department of Surgery, 2020)
Background: In paediatric trauma, measured increase in prevertebral soft tissue thickness on a lateral cervical spine (C-spine) X-ray is interpreted as swelling, raising suspicion of C-spine injury1,2 . Defining swelling in absolute measurements is cumbersome – children’s sizes vary. Evidence for potentially more consistent tools measuring soft tissue thickness as a ratio of vertebral body width is lacking. Clinical decision rules should be based on best available evidence to minimize patient harms and improve health outcomes. This study determined whether consistent, measurable ratios exist for use as simple diagnostic tools in assessing paediatric soft tissue swelling and C-spine injury. Methods: A pragmatic quantitative retrospective cross-sectional study randomly sampled C-spine trauma X-rays taken at a South African children’s hospital. Seventy-one un-intubated X-rays from 85 controls were used to identify normal ratios. The authors measured vertebral bodies and soft tissue at each level, created all possible ratios, then chose the two least variable – one for the upper and one for the lower C-spine. Twenty cases aided in determining diagnostic accuracy for C-spine injury. Results: Mean soft tissue at the second cervical vertebral level (c2) was 38% of the seventh vertebra (C7) (95%CI:34-41.9%, SE:2.0%, variance:2.5%). Mean c6 soft tissue was 65.6% of C7 vertebra (95%CI:61.9-69.3%, SE:1.9%, variance:2.3%). In diagnosing C-spine injury, a Receiver Operating Characteristic (ROC) curve calculation gave an empirical optimal cut-point of 53.9% and 74.4% respectively. Using practical cut-offs of 55% at c2 and 75% at c6 yield specificities of 93.8% (95%CI:84.8-98.3%) and 81.8% (95%CI:70.4-90.2%), with negative predictive values of 90.9% (95%CI:81.3-96.6%) and 91.5% (95%CI:81.3-97.2%) respectively. Conclusions: Consistent and specific ratios exist in the upper and lower paediatric C-spine. Both ratios have extremely poor sensitivities and positive predictive values and so are poor screening tools, but can aid in ruling in injury in patients with clinical suspicion. Level of evidence: Diagnostic Level III